Assessing greenhouse gas emission from waste management in EU countries - Zhang, Chunmin (2012)
Waste management plays an important role in reducing greenhouse gas (GHG) emission. The purpose of this study is to explore the economic, social and envi-ronmental factors that could significantly affect GHG emission from waste management in European Union countries. Based on the cross-section data in 2008 among European Union countries, three components (significant factors) were extracted from 12 possible factors by the principal component analysis. Also, the relation between GHG emission from waste sector and significant fac-tors was quantified through the multiple linear regression. On one hand, the results demonstrated that 42.4% of the GHG emission from waste sector could be explained by two significant factors: Component 1 (external issues from economy, society and environment) and Component 2 (internal issues from waste management and environmental awareness). On the other hand, the find-ings indicated that Component 3 (the waste from waste management) could not statistically explain the GHG emission from waste sector. However, the exact contribution of each possible factor to GHG emission is still unknown and the other 57.6% of the GHG emission from waste sector has not been ascertained. Therefore, further research might concentrate on investigating how GHG emis-sion has been affected by each possible factor, as well as exploring other undis-covered factors that could affect the GHG emission from waste management.